Whose rights? Which representation? Conceptual problems concerning the representation of the ‘rights’ of future generations - Tattay Szilárd (HUNGARIAN JOURNAL OF LEGAL STUDIES, 2024)
The legal conceptualisation of upcoming generations and their specific rights raises important theoretical issues and constitutes a special challenge to jurisprudence in general and legal philosophy in particular. Not even the most essential questions regarding the legal situation of unborn generations have been settled yet. Are future generations capable of being holders of rights? And if so, how can we conceptualise their rights? Can we use the conventional rights theories for that purpose? What does it mean and how is it possible to ‘represent’ the rights or interests of future generations? What kind of rights or interests can be attributed at all to not-yet-existing people? Can we identify the interests of future generations, and if so, how can we specify them? In this paper I will endeavour to address the questions raised above and make an attempt to offer an adequate conceptual framework for their analysis by merging two quite distinct theoretical discourses which are seldom combined: the legal theoretical discourse on the nature, scope and holders of rights, and the moral philosophical branch of the multifaceted discourse on intergenerational justice.